Groundwater Potential Investigation Using Electrical Resistivity Method in BASUG New Site Main Campus Gadau, Bauchi State, Nigeria - Shehu, Fatima; Yusuf Idi, Bello; Abubakar, Dauda; Muhammad, Shehu; Adamu Gadau, Shamsuddeen (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
The study examined the use of vertical electrical sounding (VES) method for groundwater potential investigation in BASUG New Site Faculty of Science Main Campus Gadau, Itas/Gadau L.G.A, Bauchi State. The 12 VES points were carried out across the study area using the Schlumberger electrodes arrays with current electrodes separation from 0 to 200 m to each profile of VES points to identify the depths and resistivity value of the identified geo-electric layers. Through analysis using interpex software, the apparent resistivity; depth and thicknesses of the aquifer were generated. The Interpreted geo-electric layers show a sequence of lateritic topsoil, coarse sand, silty sand, clay sand and clayey. Result of the VES curve analysis reveals that the sub-surface is underlained by three to four lithological layers namely; topsoil, coarse sand, silty sand, and clay sand 0-50m, each VES point is 50m that is one profile is 200m.